2019
DOI: 10.1609/hcomp.v7i1.5273
|View full text |Cite
|
Sign up to set email alerts
|

Who Is in Your Top Three? Optimizing Learning in Elections with Many Candidates

Abstract: Elections and opinion polls often have many candidates, with the aim to either rank the candidates or identify a small set of winners according to voters’ preferences. In practice, voters do not provide a full ranking; instead, each voter provides their favorite K candidates, potentially in ranked order. The election organizer must choose K and an aggregation rule. We provide a theoretical framework to make these choices. Each K-Approval or K-partial ranking mechanism (with a corresponding positional sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…However, (Goel et al 2019) suggests that knapsack voting was less burdensome in practice and desirables strategic properties. In (Garg et al 2019) learning rates were proposed to identify optimal ballot design, concluding that the threshold K was historically set too low in Kapproval voting for optimal learning. A study into the effect of K-approval, threshold-approval, K-ranking (in two variations), knapsack and K-token voting with recruited crowdworkers evaluated the effect on cognitive load and voters' ability to recall their stated preferences (Fairstein, Benade, and Gal 2023), suggesting Value-for-Money ranking as cognitively the hardest on voters.…”
Section: Related Workmentioning
confidence: 99%
“…However, (Goel et al 2019) suggests that knapsack voting was less burdensome in practice and desirables strategic properties. In (Garg et al 2019) learning rates were proposed to identify optimal ballot design, concluding that the threshold K was historically set too low in Kapproval voting for optimal learning. A study into the effect of K-approval, threshold-approval, K-ranking (in two variations), knapsack and K-token voting with recruited crowdworkers evaluated the effect on cognitive load and voters' ability to recall their stated preferences (Fairstein, Benade, and Gal 2023), suggesting Value-for-Money ranking as cognitively the hardest on voters.…”
Section: Related Workmentioning
confidence: 99%
“…Ballot length has been considered in con- texts other than IRV-for instance, research on the Boston school choice mechanism found that limiting the number of schools parents could rank to five resulted in undesirable strategic behavior (Abdulkadiroglu et al 2006). There has also been research on ballot length in approval voting from a learning theory angle, seeking to recover a population's preferences efficiently (Garg et al 2019).…”
Section: Related Workmentioning
confidence: 99%